JALUR REMPAH DAN ISLAMISASI NUSANTARA: : Jaringan Samudera Pasai abad XIII – XVI - Abd. Rahman Hamid (Jurnal Masyarakat dan Budaya, 2021)
T This article analyses the connection between the spice route and the Islamization of the Nusantara archipelago, focusing on the Samudera Pasai network. This research is historical research that uses several sources from Malay, Arabic, Chinese, and Portuguese. The research found that the Samudera Pasai use the decline of the Sriwijaya network to create a hub of a new network of the Malacca Strait, Indian Ocean, and the Java Sea at the northern tip of Sumatra. After the king converted to Islam and made his country a center for religious da'wah, Samudera Pasai grew more rapidly. From this process, two patterns were formed, namely the India-China network and the Java-Malacca network. The first pattern is highly influenced by India's religious and commercial characteristics, while China tends to have political and trade characteristics. In this pattern, Samudera Pasai is passive and becomes part of two main poles of the Asian economy (India and China). In the second pattern, Samudera Pasai is more serious in pushing Muslim communities and the birth of Islamic leaders in Java. Samudera Pasai network largely determined the progress of Malacca. After the kingdom converted to Islam because of the enforcement of the Sultan of Pasai and the scholars in Malacca, Samudera Pasai finally replaced the primary role of the Malacca Strait. This study concludes that Islam is a stimulus for the growth and development of Muslim port cities in the archipelago's spice routes in the XIII-XVI centuries.